Lifetime overweight and adult asthma: 1978/1979 Ribeirão Preto Birth Cohort, São Paulo, Brazil - Luana Lopes Padilha; Cecilia Claudia Costa Ribeiro; Joelma Ximenes Prado Teixeira Nascimento; Vanda Maria Ferreira Simões; Fernanda Pino Vitti; Viviane Cunha Cardoso; Elcio Oliveira Vianna; Marco Antônio Barbieri; Antônio Augusto Moura da Silva; Heloísa Bettiol (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Studies focusing on obesity and asthma frequently consider the weight at a given time; thus, modeling pathways through lifetime overweight may contribute to elucidate temporal aspects in this relationship. This study modeled the pathways in the association of lifetime overweight with asthma in adult life, using data from the 1978/1979 Birth Cohort, Ribeirão Preto, São Paulo, Brazil (n = 2,063) at birth (baseline), school age (9/11 years) and adult age (23/25 years). A theoretical model was proposed to explore the effects of lifetime overweight on asthma in adult life analyzed by structural equation modeling. Parental obesity (SC - standardized coefficenttotal = 0.211, p < 0.001; SCdirect = 0.115, p = 0.007) and overweight at school age (SCtotal = 0.565, p < 0.0001; SCdirect = 0.565, p < 0.0001) were associated with overweight in adult life. Parental obesity (SCdirect = 0.105, p = 0.047) and nutritional status at birth (SCtotal = -0.124, p = 0.009; SCdirect = -0.131, p = 0.007) were associated with asthma in adult life. A higher "current adult socieconomic situation" was inversely associated to overweight (SCdirect = -0.171, p = 0.020) and to asthma in adult life (SCtotal = -0.179, p = 0.041; SCdirect = -0.182, p = 0.039). Parental obesity showed a transgenerational effect in weight, triggering to childhood and adulthood overweight. Parallel to underweight at birth, parental obesity was also a risk to asthma in adult life. While, the socioeconomic status in adult life protected from both, overweight and asthma.